Intelligent Approach for School Teacher Recruitment: Distributing IT Subjects Based on Multiple Attributes - Mohammed, Mohannad T.; Shubber, Mohamed Safaa; Jalood, Nawar S.; Jasim, Ali N.; Shareef, Ali H.; Garfan, Salem (Applications of Modelling and Simulation, 2023)
Choosing suitable IT courses for potential applicants or graduates based on their academic performance (GPA) and soft skills is a multicriteria decision-making (MCDM) problem due to three factors: multiple evaluation criteria, uncertain importance levels of these criteria and data variability. In this study, data from 80 Bachelor of Education (Information Technology) honour graduates (AT20) at Sultan Idris Education University’s School of Art, Computing and Creative Industry in 2017 was analysed. A decision matrix was constructed for each applicant based on the analysed data. The analytic hierarchy process (AHP) and VIseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) methods were used to determine the criteria weights and rank the IT subjects for each applicant, respectively. Results indicated the following: (i) AHP effectively allocated weights to the evaluation criteria, with GPA receiving the highest weight of 0.708 and soft skills obtaining a weight of 0.292. (ii) The integration of AHP and VIKOR (intelligent approach) efficiently ranked each IT subject for each applicant and assigned the highest-ranked subject to the applicants. A systematic ranking was conducted to validate the proposed results. Selecting IT subjects for graduates based on GPA and soft skills can considerably affect the quality of education, the success of schools and the professional development of individual educators. By incorporating these factors into the hiring process, educational institutions can foster more diverse, adaptable and high-performing teaching staff applicants.